Role of Elastography in Early Detection of Liver Cirrhosis - Susanto, David; Irawan, Visakha R (Journal of Medicine and Health, 2017)
Liver cirrhosis is a condition in which the liver slowly deteriorates and is unable tofunction usually due to chronic, or long lasting, injury. Fibrotic tissue replaces healthy livertissue and partially blocks the flow of blood through the liver. Fibrosis increases liver stiffness.Liver palpation on the early physical examination has been used to assess liver stiffness.Though, palpation has some limitations, such as highly subjective, very operator dependent,and sometimes even impossible to perform. At present, liver biopsy remains the current goldstandard for assessing liver fibrosis, even though the diagnostic accuracy is limited by thespecimen size, invasive procedure, and long duration for getting the result. Elastography is analternative method to liver biopsy in patients with chronic liver disease.Keywords: chronic liver disease, elastography, liver cirrhosis